Exploring HIV Testing Models for Differentiated Service Delivery in Southern Africa: A Systematic Review - Hamufare Dumisani Mugauri; Mujinga Karakadzai; Owen Mugurungi; Joconiah Chirenda; Kudakwashe Takarinda; Mufuta Tshimanga (Shahid Sadoughi University of Medical Sciences, 2023)
Background: Targeting HIV testing services, as the World Health Organization (WHO) recommended in 2015, fast-tracks the identification of individuals with HIV and addresses the persisting HIV testing gap which might delay epidemic control. Following this recommendation, different models of targeted testing have been implemented, exposing varied interpretations by different countries. This study identifies, aggregates, and synthesizes targeted HIV testing models to develop a concise targeted testing package which can increase the identification of people with HIV. Methods: A systematic literature search in PubMed, Scopus and Web of Science databases identified cross-sectional studies of people (18 years and above) from Southern Africa published between 2016 and 2021. Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were applied, and the quality of studies was evaluated using the Joanna Brigs Institute tool (JBI). Data were extracted using a guided matrix to identify the target population, testing models, description, and positivity ratio. Conclusions and methodological suggestions were narratively synthesized. Results: The authors identified 574 studies; 42 full-text articles were screened which yielded 29 studies of moderate quality (71%) meeting the eligibility criteria. Of these, 25 studies (86.2%) were quantitative. From the included studies, similar models were synthesized, and 12 targeted testing models emerged. Prioritized models were Index testing, described in 3 (10.3%) of the studies, scoring the highest positivity ratio of >30%. Six studies (20.7%) described male-targeted models with yields influenced by age, economic status, and educational level, with a positivity ratio of 10% among first-time testers. In contrast, four (13.8%) described Key and Vulnerable Populations (KVP) focused models (positivity ratio of 37.5%) and recency-informed targeted testing (13.1% positivity ratio). Conclusion: This review provides a critical overview and insights into the targeted testing models implemented in Southern Africa. Synthesizing comparable models can meet the various needs of unique populations comprehensively and increase positivity ratio. The recommended models can improve the efficiency of programs in targeting HIV testing services.